Passive Tubular Daylight Guidance System Survey. (2016) - Ciugudeanu, Calin; Beu, Dorin
Abstract: Daylight levels decrease asymptotically with distance from the window so that a disproportionate amount of daylight/solar gain must be introduced into the front of the room to achieve small increases in daylight deep inside at the back. Several systems exist to redirect daylight into areas of buildings that cannot be lit by traditional glazing. One major generic group is known as 'beam daylight' - redirects sunlight by adding reflective or refracting elements to conventional windows. The second major group is known as Tubular Daylight Guidance Systems (TDGS). Tubular daylight guidance systems are linear structures that channel daylight by means of optical interactions into the core of a building. The paper presents a case-study for a passive TDGS installed in a residential building in Cluj-Napoca, Romania. Field measurements are presented as well as software simulation results (DIALux, Lux Calculator). Based on the official numbers of dwellings provided by the Romanian National Institute of Statistics and the energy savings presented in the case-study, some predictions were made regarding the energy saving potential of passive tubular daylight systems over Romania.